Inhibitor development in nonsevere hemophilia: data from the European Haemophilia Safety Surveillance (EUHASS) registry - Kathelijn Fischer; Riitta Lassila; Flora Peyvandi; Alexander Gatt; Samantha C. Gouw; Robert Hollingsworth; Thierry Lambert; Radek Kaczmarek; Diana Carbonero Alvarez; Michael Makris (Research and Practice in Thrombosis and Haemostasis)
Background: Information on inhibitor development in nonsevere hemophilia and its association with clotting factor concentrate type is limited. Objectives: To assess inhibitor development in patients with nonsevere hemophilia A (HA) and hemophilia B (HB) in the European Haemophilia Safety Surveillance system. Methods: Inhibitors and total treated patients are reported annually. Any exposure to concentrate per year was considered a treatment year. Incidence rates per 1000 treatment years and 95% CIs were calculated according to type of concentrate and compared using incidence rate ratios (IRRs). Results: During 2008 to 2023, 90 centers reported on 36,074 (HA) and 9238 (HB) treatment years. The inhibitor rate for nonsevere HA receiving factor (F)VIII was 4.2 per 1000 treatment years (95% CI, 3.5-4.9). Inhibitors developed at median 47.5 years (P25-P75 [IQR], 17.0-69.0), after median 40 exposure days (EDs; IQR, 17-80), with 58% occurring <50 EDs and 88% <100 EDs. Overall, 4 of 149 (2.7%) patients in the inhibitor group were female. Only one inhibitor was reported in nonsevere HB, in a female patient (FIX 7%, after 6 EDs), resulting in an inhibitor rate of 0.1 per 1000 treatment years (95% CI, 0.0-0.6). Compared with standard half-life recombinant FVIII, inhibitor rates on both plasma-derived FVIII (IRR, 0.27; 95% CI, 0.11-0.58; P < .001) and extended half-life FVIII (IRR, 0.18; 95% CI, 0.02-0.68; P = .002) were significantly reduced. Conclusion: Inhibitors in nonsevere hemophilia occurred at a rate of 4.2 per 1000 treatment years in HA and 0.1 per 1000 treatment years in HB. Compared with standard half-life FVIII, inhibitor development on plasma-derived and extended half-life FVIII were reduced. These data show that inhibitor monitoring is relevant with nonsevere HA in both sexes and should be continued lifelong.